A method for preparing silicon-aluminum composite oxide spheres
By adding high-content silicon oxide to the oil ammonia column molding method and controlling the sol viscosity, combined with step-by-step drying and calcining, silicon-aluminum composite oxide pellets with large specific surface area and pore volume and high compressive strength were prepared, which solved the problems of insufficient performance of small balls in the existing technology and complex preparation process, and achieved efficient catalytic and adsorption performance.
Patent Information
- Application Number
- CN202310346168.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-04-03
AI Technical Summary
In the prior art, the specific surface area and pore volume of silicon-aluminum composite oxide pellets are low, resulting in low dispersion of active components in catalyst applications, reduced stability and service life, and complex preparation process and high cost.
By adding high-level silicon oxide to the oil ammonia column molding method, the stirring time and temperature are controlled, and a silicon-aluminum sol with a sol viscosity of 800-1000mPa·S is formed. Step-by-step drying and step-by-step calcining are used to prepare silicon-aluminum composite oxide pellets with large specific surface area and pore volume and high compressive strength.
The specific surface area and pore volume of silicon-aluminum composite oxide spheres are significantly improved, their adsorption properties and catalytic activity are enhanced, and their carbon deposit resistance and liquid water resistance are improved. At the same time, the preparation process is simplified and production costs are reduced.
Smart Images

Figure BDA0004159798120000091 
Figure BDA0004159798120000101 
Figure BDA0004159798120000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation, and in particular to a method for forming and preparing silicon-aluminum composite oxide spheres. Background Art
[0002] Silica-aluminum composite oxides are a type of chemical with large consumption, and are widely used as carriers and raw materials for catalysts in oil refining, chemical industry and petrochemical industry. In addition, the rich pore structure of silica-aluminum composite oxides gives them good adsorption capacity, and they are widely used in gas purification technology and high-efficiency drying technology in the fields of military industry, pharmaceuticals, metallurgy, industrial catalysis, etc.
[0003] Among the industrial methods for forming spherical particles, the oil-ammonia column forming method has the advantages of high sphericity, good particle uniformity, low wear rate, controllable particle size and relatively high strength. It has become one of the main methods for preparing alumina and silicon-containing alumina spheres.
[0004] In the technologies disclosed in CN 103011213 B, US 2805206 B, CN 101935060 A, and CN 1204964C, soluble aluminum salt is used as raw material, and the obtained aluminum sol is dripped into an oil-ammonia column to form. After aging, drying, and roasting, the specific surface area of the prepared alumina sphere is 230m 2 / g, and the pore volume is about 0.4cm 3 / g. In adsorbent applications, the low specific surface area and pore volume of alumina beads will reduce the adsorption capacity. In catalyst applications, the low specific surface area of alumina beads is not conducive to the high dispersion of active components, and it is easy to cause sintering of active components in high-temperature reactions. The low pore volume reduces the mass transfer effect, and a large amount of carbon deposits are formed during the regeneration process, which leads to a decrease in catalyst stability and service life. Therefore, it is necessary to modify the alumina beads to increase the specific surface area and pore volume and improve the anti-carbon deposition performance.
[0005] CN 105478100 A discloses a method for preparing silicon-containing alumina beads, in which aluminum hydroxide powder is slurried, diluted nitric acid, urea, sodium silicate, kerosene and fatty alcohol polyoxyethylene ether are added, and the beads are dropped into an oil-ammonia column to form beads. In this method, the silicon content accounts for only 0.3% of the mass of the alumina. The patent does not provide performance index parameters such as the specific surface area and pore volume of the silicon-containing alumina beads, and does not compare the performance differences of the catalyst before and after the modification.
[0006] CN 1019502 B reports a method for preparing silicon-containing alumina spheres, wherein aluminum trichloride and acidified water glass are prepared into a mixed acidic solution, the silicon oxide content is 5-10%, the solution is gelled with an ammonia solution containing 10% ammonia, after aging and separation, it is washed and kneaded with inorganic acid to form a pseudo solution, and then formed by oil-ammonia column. In this method, when the silicon oxide content is 7.5%, the specific surface area is 256m 2 / g, pore volume is 0.58cm 3 / g, it can be seen that the modification effect of low content of silicon oxide is not obvious. This is because the drying temperature is above 100℃, the wet rubber balls shrink too fast, so that some smaller pores are sealed, resulting in the loss of specific surface area and pore volume.
[0007] CN 1089032 C discloses a porous silicon-containing alumina carrier ball and a method for preparing the same. The method comprises mixing an acidic aluminum chloride solution with an acidified sodium silicate solution, neutralizing the mixture with ammonia water, washing and filtering the mixture, and then adding an inorganic acid for peptization. The prepared silicon-containing alumina wet peptoid ball is dried at low temperature in an atmosphere containing ammonia. During the drying process of the wet peptoid ball, the ammonia in the atmosphere is adsorbed on the wet peptoid ball, slowing down the rapid bonding of the alumina particles and helping to increase the pore volume of the ball. The specific surface area of the prepared silicon-containing alumina is 280-360 m 2 / g, pore volume is 0.6-0.8ml / g. However, the silicon oxide content in this method is 5-15%, and the low content of silicon oxide has limited improvement on the specific surface area and pore volume of the small ball. In addition, the volatilization of ammonia during the drying process of the wet rubber ball causes environmental pollution, which is limited in industrial production.
[0008] The above technology shows that compared with alumina spheres, the specific surface area and pore volume of silicon-containing alumina spheres have increased, but the low content of silicon oxide has limited room for improvement in alumina spheres. Therefore, for the oil-ammonia column molding method to prepare silicon-alumina composite alumina spheres, how to effectively increase the specific surface area and pore volume, improve the anti-carbon deposition performance, simplify the preparation process, and reduce the production cost are the difficulties in the research of silicon-alumina composite oxide spheres. Summary of the invention
[0009] The purpose of the present invention is to overcome at least one of the defects of the above-mentioned prior art and to provide a method for forming and preparing silicon-aluminum composite oxide spheres with large specific surface area and pore volume, high compressive strength, good anti-carbon deposition performance and resistance to liquid water.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] The preparation method of silicon-aluminum composite oxide spheres provided by the present invention greatly improves the specific surface area and pore volume of silicon-aluminum composite oxide spheres by adding a high content of silicon oxide, enriches the pore structure, and improves the anti-carbon deposition performance. In the oil-ammonia column molding method, the properties of the sol play a key role in the performance of the spherical particles. Therefore, in the present invention, the sol viscosity of the silicon-aluminum sol is maintained at 800-1000mPa·S by controlling the stirring time, stirring temperature, and the amount of inorganic acid. Too low sol viscosity will lead to a low balling rate and poor strength of the sphere sample, while too high sol viscosity will cause the sol to be unable to drip smoothly during the dripping process, often in a strip shape, which significantly reduces the sphericity. In addition, the wet colloid spheres after molding are dried and calcined in steps to prevent the rapid high-temperature drying and calcining from causing the spheres to shrink sharply and cause the pores to collapse, thereby avoiding the loss of specific surface area and pore volume.
[0012] The silicon-aluminum composite oxide pellets of the present invention are prepared by an oil-ammonia column molding method. The raw materials include a silicon source, an aluminum source, and an inorganic acid. The oil-ammonia column is composed of an upper oil phase and a lower ammonia phase. The mass content of SiO2 in the silicon-aluminum composite oxide pellets is 20-96%, the mass content of Al2O3 is 4-80%, and the specific surface area is 300-600m 2 / g, pore volume is 0.5-0.9cm 3 / g, compressive strength ≥60N / particle, with good anti-carbon deposition performance, and liquid water resistance. The specific plan is as follows:
[0013] A method for forming and preparing silicon-aluminum composite oxide spheres, the method comprising the following steps:
[0014] Mixing the silicon source and the aluminum source evenly in water to obtain a silicon-aluminum mixed solution;
[0015] Adding inorganic acid to the silicon-aluminum mixed solution, gradually forming a sol through stirring, and continuing stirring until the sol viscosity reaches 800-1000mPa·S;
[0016] The sol is dripped into an oil-ammonia column molding device for molding, aged in an ammonia water phase, and then dried and calcined in steps to obtain silicon-aluminum composite oxide pellets.
[0017] Furthermore, the silicon source includes one or more of silica sol, sodium silicate or silicon oxide powder.
[0018] Furthermore, the aluminum source includes one or more of aluminum sol, pseudo-boehmite, aluminum hydroxide, sodium aluminate or aluminum oxide powder.
[0019] Furthermore, the silicon source and the aluminum source are used in such amounts that the mass content of SiO2 in the aluminum composite oxide pellets is 20-96%, and the mass content of Al2O3 is 4-80%.
[0020] Furthermore, the inorganic acid includes one or more of nitric acid, hydrochloric acid or sulfuric acid, and the mass concentration of the inorganic acid is 3-25%.
[0021] Furthermore, H + The molar ratio of (SiO2+Al2O3) in the silicon source and the aluminum source is (0.1-2.0):1.
[0022] Furthermore, the oil phase in the oil-ammonia column forming device includes one or more of petroleum ether, kerosene, hexane, heptane, octane or gasoline, and the height of the oil phase is 1-3 mm.
[0023] Furthermore, in the oil-ammonia column forming device, the mass concentration of aqueous ammonia is 5-25%, the height of the aqueous ammonia phase is 5-15 cm, and the aging time is 5-24 h.
[0024] Furthermore, the ambient temperature during continued stirring is not higher than 80°C.
[0025] Furthermore, the specific process of step-by-step drying is: drying at 30°C for 3-5h, drying at 50°C for 3-5h, drying at 80°C for 3-5h, and drying at 100°C for 8-12h;
[0026] The specific process of step-by-step calcination is: calcination at 200°C for 2-5h, calcination at 400°C for 2-5h, and calcination at 600°C for 4-8h.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The silicon-aluminum composite oxide pellets of the present invention contain a high content of SiO2, which can greatly increase the specific surface area and pore volume compared with alumina pellets and silicon-aluminum pellets with low silicon content, and help improve the adsorption performance of the silicon-aluminum composite oxide pellets. In catalyst applications, the larger specific surface area helps to improve the dispersion of the active components of the catalyst, and improve the catalyst activity and stability;
[0029] (2) The silicon-aluminum composite oxide pellets of the present invention are dried and calcined in steps, so that the silicon-aluminum composite oxide pellets gradually shrink during the drying and calcining process. On the one hand, this avoids the collapse of the pores caused by rapid high-temperature drying and calcining, thereby reducing the loss of specific surface area and pore volume. On the other hand, this helps to improve the strength of the silicon-aluminum composite oxide pellets and avoids the problems of pellet adhesion, deformation, breakage, cracks, etc. caused by rapid drying and calcining.
[0030] (3) The silicon-aluminum composite oxide pellets of the present invention are resistant to liquid free water and will not break or pulverize when used in a condition with a high free water content. Repeated immersion in free water has no significant effect on the pore structure and strength of the silicon-aluminum composite oxide pellets.
[0031] (4) The silicon-aluminum composite oxide beads of the present invention have a large number of micropores and mesoporous structures. The rich pore structure is conducive to efficient and rapid adsorption and desorption. It is not easy to cause pore blockage during repeated regeneration and has good anti-carbon deposition performance.
[0032] (5) The preparation process of the silicon-aluminum composite oxide pellets of the present invention does not require the addition of surfactants, additives, etc., and does not introduce impurities. The prepared silicon-aluminum composite oxide pellets have high purity, and the preparation process is simple, the production cost is low, and they are easy to industrialize. DETAILED DESCRIPTION
[0033] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0034] A method for forming and preparing silicon-aluminum composite oxide spheres comprises the following steps:
[0035] (1) Weigh a certain amount of silicon source and aluminum source, use water as solvent, and stir to mix evenly; the silicon source is selected from one or more of silica sol, sodium silicate, and silicon oxide powder; the aluminum source is selected from one or more of aluminum sol, pseudo-boehmite, aluminum hydroxide, sodium aluminate, and aluminum oxide powder; the SiO2 mass content in the aluminum composite oxide pellets is 20-96%, and the Al2O3 mass content is 4-80%.
[0036] (2) Weigh a certain amount of inorganic acid, add it to the silicon-aluminum mixed solution, gradually form a sol through stirring, and continue stirring at room temperature to 80° C. until the sol viscosity reaches 800-1000 mPa·S; the inorganic acid is selected from one or more of nitric acid, hydrochloric acid, and sulfuric acid, the molar ratio of H+ to SiO2+Al2O3 in the inorganic acid is 0.1-2.0, and the mass concentration of the inorganic acid is 3-25%.
[0037] (3) dripping the sol in (2) into an oil-ammonia column forming device for forming, aging in an ammonia phase for 5-24 hours, and then drying and calcining in steps to obtain silicon-aluminum composite oxide pellets. The oil phase is selected from one or more of petroleum ether, kerosene, hexane, heptane, octane, and gasoline. The height of the oil phase in the oil-ammonia column forming device is 1-3 mm, the mass concentration of ammonia is 5-25%, and the height of the ammonia phase is 5-15 cm; drying in steps, drying at 30°C for 3-5 hours, drying at 50°C for 3-5 hours, drying at 80°C for 3-5 hours, and drying at 100°C for 8-12 hours; the stepwise calcining is calcining at 200°C for 2-5 hours, calcining at 400°C for 2-5 hours, and calcining at 600°C for 4-8 hours.
[0038] Example 1
[0039] A method for forming and preparing silicon-aluminum composite oxide spheres comprises the following steps:
[0040] Weigh 5.828g of pseudo-boehmite powder (alumina content is 70%), add 13g of deionized water, stir until dissolved, weigh 3.921g of silica sol (SiO2 content is 30.6%), add to the pseudo-boehmite solution, stir for 30 minutes, add 18.9g of 10% nitric acid solution dropwise, stir at room temperature for 1h, the viscosity of the silica-alumina sol reaches 800-1000mPa·S.
[0041] The oil phase of the oil-ammonia column is petroleum ether, the oil layer height is 2mm, the ammonia concentration in the ammonia phase is 8%, and the ammonia phase height is 12cm. The prepared silicon-aluminum sol is dripped into the oil-ammonia column drop by drop, taken out after aging for 24 hours, dried at 30°C for 4 hours, dried at 50°C for 4 hours, dried at 80°C for 4 hours, dried at 100°C for 10 hours, and calcined in a muffle furnace at 200°C for 3 hours, 400°C for 3 hours, and 600°C for 6 hours to obtain silicon-aluminum composite oxide pellets.
[0042] Example 2
[0043] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 7.843 g, the amount of 10% nitric acid solution was 25.2 g, and the mixture was stirred at room temperature for 2 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0044] Example 3
[0045] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 15.686 g, the amount of 10% nitric acid solution was 37.8 g, and the mixture was stirred at room temperature for 3.5 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0046] Example 4
[0047] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 39.215 g, the amount of 10% nitric acid solution was 75.6 g, and the mixture was stirred at 40°C for 3 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0048] Example 5
[0049] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 54.902 g, the amount of 10% nitric acid solution was 100.8 g, and the mixture was stirred at 60°C for 2 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0050] Example 6
[0051] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 78.431 g, the amount of 10% nitric acid solution was 138.6 g, and the mixture was stirred at 80°C for 2 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0052] Example 7
[0053] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 156.863 g, the amount of 10% nitric acid solution was 264.6 g, and the mixture was stirred at 80°C for 5 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0054] Example 8
[0055] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content: 30.6%) was 274.510 g, the amount of 10% nitric acid solution was 453.6 g, and the mixture was stirred at 80°C for 8 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0056] Example 9
[0057] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the aging time of the silica-alumina sol in the ammonia water phase was 5 hours.
[0058] Example 10
[0059] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the aging time of the silica-alumina sol in the ammonia water phase was 8 hours.
[0060] Embodiment 11
[0061] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the aging time of the silica-alumina sol in the ammonia water phase was 12 h.
[0062] Example 12
[0063] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the aging time of the silica-alumina sol in the ammonia water phase was 18 h.
[0064] Example 13
[0065] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 3.78 g, and the mixture was stirred at 60° C. for 4 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0066] Embodiment 14
[0067] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 9.45 g, and the mixture was stirred at 40° C. for 3 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0068] Embodiment 15
[0069] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 37.80 g, and the mixture was stirred at room temperature for 0.5 h. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0070] Example 16
[0071] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 75.60 g, and the mixture was stirred at room temperature for 10 min. The viscosity of the silica-alumina sol reached 800-1000 mPa·S.
[0072] Comparative Example 1
[0073] A method for forming and preparing oxide spheres comprises the following steps:
[0074] Weigh 5.828g of pseudo-boehmite powder (alumina content of 70%), add 13g of deionized water, stir until dissolved, add 12.6g of 10% nitric acid solution dropwise, stir at room temperature for 1h, and the viscosity of the aluminum sol reaches 800-1000mPa·S.
[0075] The oil phase of the oil-ammonia column is petroleum ether, the oil layer height is 2mm, the ammonia concentration in the ammonia phase is 8%, and the ammonia phase height is 12cm. The prepared aluminum sol is dripped into the oil-ammonia column drop by drop, aged for 24 hours, taken out, dried at 30°C for 4 hours, 50°C for 4 hours, 80°C for 4 hours, 100°C for 10 hours, and calcined in a muffle furnace at 200°C for 3 hours, 400°C for 3 hours, and 600°C for 6 hours to obtain alumina balls.
[0076] Comparative Example 2
[0077] A method for forming and preparing oxide spheres comprises the following steps:
[0078] Weigh 7.843 g of silica sol (SiO2 content: 30.6%), add 12.6 g of 10% nitric acid solution dropwise, and stir overnight at 80°C. The viscosity of the silica sol can only reach 134 mPa·S.
[0079] The oil phase of the oil-ammonia column is petroleum ether, the oil layer height is 2mm, the ammonia concentration in the ammonia phase is 8%, and the ammonia phase height is 12cm. The prepared silica-alumina sol is dripped into the oil-ammonia column drop by drop, aged for 24 hours, taken out, dried at 30°C for 4 hours, 50°C for 4 hours, 80°C for 4 hours, 100°C for 10 hours, and calcined in a muffle furnace at 200°C for 3 hours, 400°C for 3 hours, and 600°C for 6 hours to obtain silicon oxide balls.
[0080] Comparative Example 3
[0081] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content of 30.6%) was 392.157 g, the amount of 10% nitric acid solution was 642.6 g, and the viscosity of the silica-alumina sol could only reach 635 mPa·S after stirring at 80°C overnight.
[0082] Comparative Example 4
[0083] Silica-alumina composite oxide beads were prepared according to the method of Example 1, except that the amount of silica sol (SiO2 content of 30.6%) was 1568.627 g, the amount of 10% nitric acid solution was 2532.6 g, and the viscosity of the silica-alumina sol could only reach 386 mPa·S after stirring at 80°C overnight.
[0084] Comparative Example 5
[0085] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 1.89 g, and the silica-alumina sol was stirred overnight at 80°C, and the viscosity of the silica-alumina sol could only reach 640 mPa·S.
[0086] Comparative Example 6
[0087] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the amount of 10% nitric acid solution used was 113.4 g, stirring was performed at room temperature for 2 minutes, and the viscosity of the silica-alumina sol reached 1500 mPa·S.
[0088] Comparative Example 7
[0089] Silica-alumina composite oxide beads were prepared according to the method of Example 8, except that the aging time of the silica-alumina sol in the ammonia water phase was 3 h.
[0090] Comparative Example 8
[0091] Silicon-aluminum composite oxide beads were prepared according to the method of Example 8, except that they were dried at 100° C. for 12 h and calcined in a muffle furnace at 600° C. for 6 h.
[0092] The characterization data of the silicon-aluminum composite oxide beads in each embodiment and comparative example are shown in Table 1.
[0093] Among them, the specific surface area and pore volume are obtained by BET test; the component content is obtained by XRF test; and the strength is obtained by strength tester test.
[0094] Table 1 Characterization data of silicon-aluminum composite oxide pellets
[0095]
[0096]
[0097] As can be seen from Table 1, by comparing Example 1 with Comparative Examples 1 and 2, it can be concluded that the silicon-aluminum composite oxide spheres have a larger specific surface area and pore volume than the aluminum oxide spheres and the silicon oxide spheres, which indicates that in the oil-ammonia column forming method, the composite effect of silicon and aluminum can greatly increase the specific surface area and pore volume. By comparing Examples 1-8 with Comparative Examples 1, 3, and 4, it can be seen that with the increase of silicon oxide content, the specific surface area and pore volume of the silicon-aluminum composite oxide spheres gradually increase. When the silicon oxide content is 94.3% and the aluminum oxide content is 5.7%, the specific surface area of the silicon-aluminum composite oxide spheres is as high as 583.7 m 2 / g, pore volume up to 0.898cm 3 / g, and when the silicon oxide content further increases, the specific surface area and pore volume of the silicon-aluminum composite oxide spheres decrease significantly.
[0098] Comparison of Comparative Examples 1 and 2 shows that in the oil-ammonia column molding method, aluminum oxide pellets are relatively easier to mold than silicon oxide pellets, and the strength of aluminum oxide pellets (62.2N / pellet) is significantly higher than that of silicon oxide pellets (25.2N / pellet). Comparison of Examples 1-8 and Comparative Examples 1, 3, and 4 shows that with the addition of silicon oxide, the strength of silicon-aluminum composite oxide pellets first increases and then decreases. When the silicon oxide content exceeds 94.3%, the strength of silicon-aluminum composite oxide pellets is lower than 60N / pellet, which indicates that after adding an appropriate amount of silicon oxide to aluminum oxide, the strength of silicon-aluminum composite oxide pellets can be improved to a certain extent.
[0099] By comparing Examples 8-12 with Comparative Example 7, it can be concluded that the aging time has relatively little effect on the specific surface area and pore volume of the silicon-aluminum composite oxide beads, but with the increase of aging time, the strength of the silicon-aluminum composite oxide beads increases. When the aging time reaches 12h or more, the strength of the silicon-aluminum composite oxide beads is basically stable at about 67N / bead.
[0100] By comparing Examples 8, 14-16 with Comparative Examples 5 and 6, it can be concluded that when the molar ratio of HNO3 to (SiO2+Al2O3) is 0.1-2.0, as the amount of HNO3 added increases, the required stirring temperature and / or stirring time can be appropriately reduced, which indicates that an appropriate amount of HNO3 added helps to form a relatively good silica-alumina sol. When the molar ratio of HNO3 to (SiO2+Al2O3) is less than 0.1, the amount of acid added is too small, resulting in a low viscosity of the silica-alumina sol. Even if the stirring temperature and stirring time are increased, the viscosity of the silica-alumina sol cannot reach 800-1000mPa·S, thereby reducing the specific surface area and pore volume of the silica-alumina composite oxide spheres, and the strength of the spheres is also significantly reduced; when the molar ratio of HNO3 to (SiO2+Al2O3) is greater than 2, the amount of acid added is too much, resulting in a high viscosity of the silica-alumina sol, resulting in the spheres being unable to drip smoothly, the sphere formation rate is low, and the particles are easy to stick together, which also leads to a decrease in strength. In addition, the viscosity of the silica-alumina sol is too high, resulting in uneven dispersion of silicon oxide and aluminum oxide, and the effect of silicon-alumina composite cannot be achieved, thereby reducing the specific surface area and pore volume of the silica-alumina composite oxide spheres. Therefore, the viscosity of the silica-alumina sol has an important influence on the performance of the silica-alumina composite oxide spheres.
[0101] By comparing Example 8 with Comparative Example 8, it can be concluded that rapid high-temperature drying and calcination cause the pore structure of the silicon-aluminum composite oxide spheres to collapse and become blocked, resulting in a significant decrease in the specific surface area and pore volume. At the same time, the moisture in the wet rubber spheres evaporates rapidly, causing the sphere particles to shrink sharply and the strength to be greatly reduced. Therefore, step-by-step drying and step-by-step calcination are one of the keys to ensuring that the silicon-aluminum composite oxide spheres have a large specific surface area, pore volume and high strength.
[0102] Water resistance test
[0103] The silicon-aluminum composite oxide pellets of Example 8 were immersed in water, taken out and placed in an oven to dry overnight at 150°C. The dried silicon-aluminum composite oxide pellets were subjected to BET and strength tests. The above operation was repeated to examine the water resistance of the silicon-aluminum composite oxide pellets. The results are shown in Table 2.
[0104] Table 2 Water resistance data of silicon-aluminum composite oxide pellets
[0105] Soaking times <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Strength (N / particle) 0 583.7 0.898 66.8 1 582.9 0.889 66.3 2 583.1 0.891 66.6 3 581.7 0.893 66.4 4 582.6 0.887 66.1 5 581.4 0.883 65.9 6 581.8 0.890 66.2 7 581.0 0.881 65.6 8 580.7 0.880 65.8 9 579.9 0.882 65.9 10 579.5 0.880 66.2
[0106] It can be seen from Table 2 that after the silicon-aluminum composite oxide beads prepared by the present invention are repeatedly immersed in water for 10 times, the specific surface area and pore volume can be maintained at more than 98% of the initial value, and the strength has no obvious change, which indicates that the silicon-aluminum composite oxide beads of the present invention have good water resistance.
[0107] Anti-carbon deposition performance test
[0108] The silicon-aluminum composite oxide pellets of Example 8 were immersed in n-hexane, taken out and placed in an oven at 250°C overnight, and the silicon-aluminum composite oxide pellets were taken out and subjected to BET and strength tests. The above operations were repeated to examine the anti-carbon deposition performance of the silicon-aluminum composite oxide pellets. The results are shown in Table 3.
[0109] Table 3 Anti-carbon deposition performance data of silicon-aluminum composite oxide pellets
[0110]
[0111]
[0112] It can be seen from Table 3 that after the silicon-aluminum composite oxide beads prepared by the present invention are repeatedly immersed in n-hexane for 10 times, the specific surface area and pore volume can be maintained at more than 86% of the initial value, and the strength has no obvious change, which indicates that the silicon-aluminum composite oxide beads of the present invention have good anti-carbon deposition performance.
[0113] In summary, the silicon-aluminum composite oxide pellets of the present invention have the advantages of large specific surface area, large pore volume, high strength, etc., are suitable for applications such as catalyst carriers and adsorbents in the petrochemical field, have good water resistance and anti-carbon deposition performance, improve the stability and service life of the silicon-aluminum composite oxide pellets, have significant economic advantages, and have broad prospects for industrial application.
[0114] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing silicon-aluminum composite oxide spheres, characterized in that: The method comprises the following steps: Mixing the silicon source and the aluminum source evenly in water to obtain a silicon-aluminum mixed solution; Adding inorganic acid to the silicon-aluminum mixed solution, gradually forming a sol through stirring, and continuing stirring until the sol viscosity reaches 800-1000mPa·S; The sol is dripped into an oil-ammonia column molding device for molding, and after aging in an ammonia water phase, it is dried and calcined in steps to obtain silicon-aluminum composite oxide pellets; The silicon source and aluminum source are used in such amounts that the mass content of SiO2 in the silicon-aluminum composite oxide pellets is 20-96%, and the mass content of Al2O3 is 4-80%; H in inorganic acid + The molar ratio of (SiO2+Al2O3) to the silicon source and the aluminum source is (0.1-2.0):1; The specific process of step-by-step drying is: drying at 30°C for 3-5h, drying at 50°C for 3-5h, drying at 80°C for 3-5h, and drying at 100°C for 8-12h; The specific process of step-by-step calcination is: calcination at 200°C for 2-5h, calcination at 400°C for 2-5h, and calcination at 600°C for 4-8h.
2. The method for preparing a silicon-aluminum composite oxide sphere according to claim 1, characterized in that: The silicon source includes one or more of silica sol, sodium silicate or silicon oxide powder.
3. The method for forming and preparing silicon-aluminum composite oxide spheres according to claim 1, characterized in that: The aluminum source includes one or more of aluminum sol, pseudo-boehmite, aluminum hydroxide, sodium aluminate or aluminum oxide powder.
4. The method for forming and preparing silicon-aluminum composite oxide spheres according to claim 1, characterized in that: The inorganic acid includes one or more of nitric acid, hydrochloric acid or sulfuric acid, and the mass concentration of the inorganic acid is 3-25%.
5. The method for forming and preparing silicon-aluminum composite oxide spheres according to claim 1, characterized in that: The oil phase in the oil-ammonia column forming device includes one or more of petroleum ether, kerosene, hexane, heptane, octane or gasoline, and the height of the oil phase is 1-3 mm.
6. The method for forming and preparing silicon-aluminum composite oxide spheres according to claim 1, characterized in that: In the oil-ammonia column forming device, the mass concentration of ammonia water is 5-25%, the height of the ammonia water phase is 5-15 cm, and the aging time is 5-24 hours.
7. The method for forming and preparing silicon-aluminum composite oxide spheres according to claim 1, characterized in that: The ambient temperature during continued stirring was not higher than 80°C.
Citation Information
Patent Citations
Method for preparing modified alumina sol suitable for oil ammonia column forming
CN101935060A
Hydrofined catalyst and preparing process thereof
CN1019502B
A method for preparing spherical alumina using an oil-ammonia column
CN103011213B
Method for preparing silicon-containing gamma-Al2O3 microsphere
CN105478100A
Porous and silicon contg. alumina carrier beads and method for making same
CN1089032C